Nitro Promoters for Selectivity Control in the Core Hydrogenation of Toluidines: Controlling Adsorption on Catalyst Surfaces. Issue 10 (12th September 2014) - Gebauer‐Henke, Ewa; Tomkins, Patrick; Leitner, Walter; Müller, Thomas E.
Abstract The diastereoselectivity in the hydrogenation of multi‐substituted aromatic ring systems was used as a sensitive tool to gain molecular‐level insight into the reaction pathways on the surface of ruthenium. Here, the hydrogenation of para‐, meta‐, and ortho‐toluidine was studied in detail. The chemoselectivity towards primary or secondary amines depends primarily on the choice of the metal; notably, nitro compounds such as NaNO2 are highly effective promoters for ruthenium catalysts, which significantly increase the chemoselectivity towards primary amines as well as catalytic activity. Lower activation energy and altered diastereoselectivity indicate that in the presence of nitro additives, the substrate molecules are adsorbed in a coordination mode favourable for the hydrogenation of the aromatic ring.